First report of Meloidogyne incognita infecting Cannabis sativa in Alabama - Lawaju, Bisho R.; Groover, William; Kelton, Jessica; Conner, Kassie; Sikora, Edward; Lawrence, Kathy S. (Journal of nematology, 2021)
Hemp ( L.) is a new crop in Alabama. In 2019, symptomatic plants with stunted growth, poor root development, and numerous galls were observed in hemp plants grown in Geneva County, AL. After harvest, soil samples were collected from areas with the symptomatic plants and root-knot nematode ( spp.) were found in the soil. Based on morphological features and the polymerase chain reactions using species-specific primers, it was identified as Further, a host differential test in a greenhouse assay confirmed it to be race 3. The pathogenicity of the nematode to the hemp was confirmed by a modified version of Koch’s postulates. To our knowledge, this is the first report of infecting in Alabama.